Analisis Faktor yang Mempengaruhi Jumlah Bakteri Escherichia coli pada Sumur Gali Penderita Diare di Kelurahan Sidomulyo Barat Kota Pekanbaru - Muchlis Muchlis; Thamrin Thamrin; Sofyan Husein Siregar (Dinamika Lingkungan Indonesia, 2017)
Raw water is water used for daily activities, which the quality has satisfied the health requirements and are consumable quality after being cooked (Permenkes No. 416 / Menkes / Per / IX / 1990). E. coli belong to a group of bacteria that are used as indicator of faecal contamination and cause human health problems like diarrhea. The purpose of this research is to determine factors that influence the amount of E. coli in the dug well. This research was conducted in West Sidomulyo village, Pekanbaru on April until October 2016. A quantitative research approach was used and cross sectional design study, by collecting 30 samples and using saturated sampling. Data that has been used in this research is primary data, which used three different survey mediums interviews, observation, and measurement of MPN raw water. The analysis of statistical test used chi-square with a significant level 5%. The results from this research from 30 respondents is 16 samples (53.3%) has groundwater indicated the presence of E. coli. Factors that has statistical significance on the number of E. coli is the distance of septictank with dug well (p value 0.003) and the physical condition of the dug well (p value 0.014). Another factors that statistically not associated with is the distance between the toilet with dug well (p value 1.000) and water-resistant depth (p value 1.000). Recomendations from this study are communities could do some water restoration by improving the lips and floor of raw water sources to water resistant. Community Health Centre of Sidomulyo required taking regular measurements of E. coli and providing counselling to the community about the septictank qualified. Nevertheless, the next researcher need to conduct research by including variables permeability and soil porosity.